Elaborating a Methodology for Gauging a Politician’s Communicative Personality - Denis S. Mukhortov; Elizaveta A. Zhovner (RUDN Journal of Language Studies, Semiotics and Semantics)
Communicative behaviour studies require using numerous methodological approaches depending on the goal and tasks of research. Linguopolitical personology conceives of political communication as an institutionalized phenomenon aimed at holding power or winning the race for power, which allows researchers to employ a particular toolset to explore a politician’s communicative behaviour. This article seeks to provide effective methods in crafting communicative types of political personality. A typology hinges upon cross-disciplinary criteria and includes seven types - The Defender, The Statist, The Servant, The Warrior, The Blame Maker, The Ruler, The Idealist, each commensurate with an overarching communicative goal and dependent lexical sets. It is tested by scrutinizing the British parliamentary debates of 2010-2022 and determining the strength of a type correlation by noun and verb frequency; to that end research exploits the Sketch Engine content analysis program. The proposed methodological algorithm, if supplemented by delving into strategies and tactics, can be regarded as a universal tool for analyzing a politician’s communicative behaviour holistically.